An implementation science protocol of the Women's Health CoOp in healthcare settings in Cape Town, South Africa: A stepped-wedge design - Wendee M. Wechsberg; Jacqueline W. Ndirangu; Ilene S. Speizer; William A. Zule; Winnifred Gumula; Courtney Peasant; Felicia A. Browne; Laura Dunlap (BMC, 2017)
Abstract Background HIV persists as a public health emergency in South Africa, especially among women of childbearing age. In response to the HIV epidemic, the Joint United Nations Programme on HIV/AIDS has put forth the 90-90-90 global goals to achieve an AIDS-free generation by 2020. This goal aspires to have 90% of people living with HIV diagnosed; 90% of those who test positive on sustained antiretroviral therapy (ART); and 90% of those on ART be virally suppressed. Ensuring access to ART is an important first step in reducing HIV incidence, especially among vulnerable populations such as women who use substances and bear the burden of HIV in South Africa. Additionally, alcohol and other drug (AOD) use and exposure to gender-based violence are associated with increased risk of HIV infection and reduced adherence to ART. However, no research has estimated ART adherence rates for women who use substances in South Africa since the government approved the provision of ART to all people living with HIV. Methods The Women's Health CoOp (WHC) is an evidence-based, woman-focused, behavioral intervention that addresses the intersecting risks of AODs, sex behaviors, and violence and victimization, with the primary goal of increasing skills and knowledge to reduce substance abuse and HIV risks and to improve ART adherence. The WHC has been packaged for further dissemination. This article describes the study protocol used to assess the feasibility and acceptability of implementing the WHC intervention into standard of care in Cape Town health clinics and substance abuse rehabilitation centers to reduce HIV risk behavior and increase ART adherence among women who use substances and are living with HIV. Discussion Because few of the interventions that demonstrate efficacy for HIV prevention and ART adherence in randomized trials are sustainable, studies to adapt and test intervention variations are needed to determine the best strategies for implementing them in real-world, high-risk settings. However, implementation in real-world settings presents challenges. Consequently, intervention developers should consider the strengths and limitations of their anticipated implementation setting by engaging with key stakeholders before, during, and after the adaptation and implementation process when developing and attempting to scale-up interventions. Trial registration NCT 02733003 and date approved 1/21/2016.